PENERAPAN VISUAL BASIC NET DAN MYSQL DALAM PENGOLAHAN DATA REKAM MEDIS STUDI KASUS PADA POLI GIGI KLINIK INTI SEHAT MEDIKA - Lestari, Ida; -, Mulyadi (JURNAL AKADEMIKA, 2020)
The basic net and mysql applications that will facilitate the dental clinic's core health clinic in the search for patient data both PBS participants and general patients along with a history of the patient's disease because data that has been integrated in a database. In research and system testing, it is carried out with several methods, namely field research, library research and laboratory research. Field research was carried out by direct observation to the health center clinic of the Dental Clinic, so that the working mechanism of the existing system was known. Literature research is done by studying books that can add to the study of science for the system and this thesis. Whereas laboratory research is carried out by creating a medical record application using VB.NeT.